Theoretical and Methodological Approaches to the Sociolinguistic Integration of Migration - Paredes García, Florentino; Sancho Pascual, María (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Migration has become a structural part of the globalized society in which we live and, as such, it is essential to determine the causes and effects it produces in the involved social groups. Sociolinguistics has a very important role to play in this respect, insofar as its object of study focuses precisely on the analysis of the interrelationships between the linguistic and the social dimensions. This volume presents a series of proposals that involve theoretical approaches, models, and applications related to the process of sociolinguistic integration in contact situations arising from migration. The volume includes studies of general interest which present models and theoretical foundations for the analysis of this process of integration, as well as others which focus on other more specific aspects, such as how migration influences the construction of individual identity, emotional and affective factors in the preservation of the heritage language, and the processes of interlingual convergence that take place in situations of migratory contact. This volume also contains the didactic dimension applied to the immigrant population, with proposals for teaching with proven effectiveness.